2023
DOI: 10.1038/s41598-023-28182-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of postoperative inclination of the joint line on clinical outcomes in total knee arthroplasty using a prosthesis with anatomical geometry

Abstract: The goal of this study was to investigate the impact of postoperative inclination of the joint line on clinical results after total knee arthroplasty (TKA) using a prosthesis with anatomical geometry. This study included 145 primary cruciate-retaining type of knee prosthesis with anatomical geometry. Three years postoperatively, clinical outcomes including the patient-reported outcomes (PROs) were recorded. Limb alignment was evaluated by the hip-knee-ankle (HKA) axis and inclination of the joint line was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…When assessing gaps intraoperatively, various studies have reported on the difference in gap size with and without trial components [8–10]. This is because with the trial implants in place, the flexion and extension gaps as well as medial tension change due to the effect of the femur component on the surrounding soft tissues [17, 23]. This was found to be true in our practice and therefore, flexion and extension gaps were routinely assessed again with the trial implants in place.…”
Section: Discussionmentioning
confidence: 99%
“…When assessing gaps intraoperatively, various studies have reported on the difference in gap size with and without trial components [8–10]. This is because with the trial implants in place, the flexion and extension gaps as well as medial tension change due to the effect of the femur component on the surrounding soft tissues [17, 23]. This was found to be true in our practice and therefore, flexion and extension gaps were routinely assessed again with the trial implants in place.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that PCL is degenerated moderately to severely in most osteoarthritic knees and may not function normally if it is retained in CR TKA. However, this is not to say that a CR design should be avoided for elderly patients because many studies have reported successful TKAs that retain a PCL [ 25 - 29 ]. A possible explanation for our observation that the ADL subscale in the PS group was superior to the CR group is that there might be patients whose PCL was severely degenerated and did not function normally in patients receiving the CR implants, considering that the mean age at operation was 76 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Double-leg standing whole-leg anteroposterior plain radiographs and single-leg standing lateral whole-leg radiographs were obtained to measure the mLDFA, MPTA, coronal HKA [20], coronal JLO [24], PTS, single-leg standing KFA, and sagittal JLO (Figure 1). The aHKA was calculated by subtracting mLDFA from MPTA [19].…”
Section: Radiographic Assessmentmentioning
confidence: 99%